Optically-controlled long-term storage and release of thermal energy in phase-change materials. Issue 1 (December 2017) - Han, Grace; Li, Huashan; Grossman, Jeffrey
Abstract Thermal energy storage offers enormous potential for a wide range of energy technologies. Phase-change materials offer state-of-the-art thermal storage due to high latent heat. However, spontaneous heat loss from thermally charged phase-change materials to cooler surroundings occurs due to the absence of a significant energy barrier for the liquid–solid transition. This prevents control over the thermal storage, and developing effective methods to address this problem has remained an elusive goal. Herein, we report a combination of photo-switching dopants and organic phase-change materials as a way to introduce an activation energy barrier for phase-change materials solidification and to conserve thermal energy in the materials, allowing them to be triggered optically to release their stored latent heat. This approach enables the retention of thermal energy (about 200 J g−1 ) in the materials for at least 10 h at temperatures lower than the original crystallization point, unlocking opportunities for portable thermal energy storage systems. Phase-change materials offer excellent thermal storage due to their high latent heat; however, they suffer from spontaneous heat loss. Han et al., use organic photo-switching dopants to introduce an activation energy barrier which enables controllable thermal energy release and retention.